Development of a predictive model for assessing the risk factors associated with recurrence following surgical treatment of chronic subdural hematoma - Chen, Min; Da, Longbiao; Zhang, Qingchao; Liu, Jie; Tang, Jian; Zha, Zhengjiang (Frontiers in Surgery, 2024)
BackgroundChronic subdural hematoma (CSDH) is a common disease in neurosurgery. Although many studies have investigated the factors affecting the recurrence of CSDH, no comprehensive prediction model has been established for the risk effect of postoperative recurrence of the disease.ObjectiveThis study aims to collect and analyze the data of CSDH patients treated in our hospital to determine the influence of preoperative, postoperative and treatment factors on the recurrence of CSDH, and to establish a corresponding prediction model to provide neurosurgeons with more accurate basis for identifying high-risk patients and guiding treatment.MethodsA total of 431 patients were collected in this study, including 323 patients who underwent traditional hematoma removal and 108 patients who underwent endoscopic hematoma removal. Relevant preoperative and postoperative data and medical history of patients were collected respectively to study the relevant factors affecting postoperative hematoma recurrence of patients, and to establish a prediction model.ResultsA total of 431 patients were enrolled in this study, 71 of whom had subdural blood recurrence. Possible relevant factors were included in univariate logistic regression, and the results showed that the preoperative GCS score, postoperative residual gas, preoperative CT hematoma thickness, coagulation function, unilateral and bilateral surgery, whether statin was taken after surgery, hematoma site, hematoma density and hematoma volume were all P < 0.2. It is a risk factor for recurrence of chronic subdural hematoma. The obtained data were further included in a multi-factor review. Six factors, including preoperative GCS score, postoperative gas residual, abnormal coagulation function, high-density hematoma, large hematoma volume, and irregular statin use after surgery, were independent risk factors for chronic subdural hematoma recurrence (P < 0.05).ConclusionThis study confirmed that six factors, including preoperative GCS score, postoperative gas residual, abnormal coagulation function, high-density hematoma, large hematoma volume, and irregular statin use, were independent risk factors for recurrence of chronic subdural hematoma. At the same time, long-term use of statins can reduce the recurrence rate of hematoma to a certain extent. In addition, the predictive model in this study could help neurosurgeons accurately identify high-risk CSDH patients.